Developing an innovation economy through clusters - Mempel-Śnieżyk, Anna; Derlukiewicz, Niki (Rozwój gospodarki innowacyjnej poprzez klastry, 2019)
The development of an innovation economy is a priority of the most highly developed countries. Poland also belongs to a group of countries whose goal is to create and strengthen the innovation of the economy and numerous activities are undertaken to achieve this. Cooperation between science and business, and cooperation between enterprises and open innovations are elements that promote innovation in the economy. The purpose of the article is to present the importance of clusters in the development of an innovation economy in Poland. Using the method of desk research, literature review, reports and data analysis and the current cluster policy in Poland are presented. Additionally, supporting cluster development as part of the Intelligent Development Operational Program is discussed, and the internationalization of clusters in Poland is presented as an important element contributing to the development of an innovation economy
Biblioteka Regionalisty, 2019, Nr 19, s. 115-129
Keywords: Dolny Śląsk